Pengaruh Inovasi, Kualitas Produk, Harga, dan Citra Merek Terhadao Keputusan Pembelian Smartphone Oppo ( Studi Kasus di Masyarakat Kabupaten Sukoharjo ) - Satrio Aji Utomo; Dr. Priscilla Uning; Santosa Tri Prabawa (STIE Wijaya Mulya, 2024)
This study aims to determine the effect of innovation, product quality, price, and brand image on purchasing decisions for Oppo smartphones in the people of Sukoharjo district. The number of samples taken was 100 respondents. The research method used is judgmental sampling in which the determination of the sample is accompanied by certain considerations. The analytical techniques used are validity test, reliability test, multiple linear regression analysis, t test, and f test using the SPSS Statistics 24 program. Based on the calculation of the t test (partial) the significance value of innovation was obtained 0.779 > 0.05. The significance value of product quality was obtained by a value of 0.000 <0.05, the price significance value was obtained by 0.000 <0.05, the brand image significance value was obtained by 0.574 > 0 ,05. While the results of the F test (simultaneous) the calculated F value is 105.454 with a significance level of 0.000. When compared with the significance value, it can be seen that the significance value on the F test is smaller than the predetermined significance value of 0.05. Based on the test results, it can be concluded that innovation partially has no effect on purchasing decisions, product quality partially influences purchasing decisions, price partially influences purchasing decisions, brand image partially has no effect on purchasing decisions and there is a simultaneous influence between innovation, product quality, price, and brand image on purchasing decisions for Oppo smartphones in the people of Sukoharjo district.Keywords: Innovation, Product Quality, Price, Brand Image, Purchase Decision